Pregunta
upstudy study bank question image url

1 Which expression ifequivalent to \( 10 k+17-7 j=10-11 k ? \) \( 0-8, k=1 \) \( 0-7 j=k-1 \) \( 0-7 j+k+1 \) \( 0-8 j-k \)

Ask by Young Robbins. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

None of the given expressions are equivalent to the original equation.

Solución

Solve the equation by following steps: - step0: Solve for \(j\): \(10k+17-7j=10-11k\) - step1: Move the expression to the right side: \(-7j=10-11k-\left(10k+17\right)\) - step2: Subtract the terms: \(-7j=-7-21k\) - step3: Change the signs: \(7j=7+21k\) - step4: Divide both sides: \(\frac{7j}{7}=\frac{7+21k}{7}\) - step5: Divide the numbers: \(j=1+3k\) To find an expression equivalent to \( 10k + 17 - 7j = 10 - 11k \), we first solve for \( j \). 1. Rearranging the equation: \[ 10k + 17 - 7j = 10 - 11k \] 2. Move all terms involving \( j \) to one side and the rest to the other side: \[ -7j = 10 - 11k - 10k - 17 \] Simplifying the right side: \[ -7j = -21k - 7 \] 3. Dividing both sides by -7: \[ j = 3k + 1 \] Now, we can express \( j \) in terms of \( k \) as \( j = 3k + 1 \). Next, we will check which of the given expressions is equivalent to this result: 1. **Expression 1:** \( 0 - 8, k = 1 \) - This does not relate to \( j \). 2. **Expression 2:** \( 0 - 7j = k - 1 \) - Rearranging gives \( 7j = 1 - k \), or \( j = \frac{1 - k}{7} \), which is not equivalent. 3. **Expression 3:** \( 0 - 7j + k + 1 \) - Rearranging gives \( 7j = k + 1 \), or \( j = \frac{k + 1}{7} \), which is not equivalent. 4. **Expression 4:** \( 0 - 8j - k \) - Rearranging gives \( 8j = -k \), or \( j = -\frac{k}{8} \), which is not equivalent. None of the provided expressions are equivalent to \( j = 3k + 1 \). Thus, the answer is that none of the expressions are equivalent to the original equation.

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To find an expression equivalent to \( 10k + 17 - 7j = 10 - 11k \), we'll rearrange the equation. First, we can move all terms involving \( k \) to one side and everything else to the other side. Rearranging gives us \( 10k + 11k = 10 - 17 + 7j \), simplifying to \( 21k = -7 + 7j \). Dividing everything by 7 gives us \( 3k = j - 1 \). From this, we can derive that \( 0 - 7j + k + 1 = 0 \), which correlates to the expression \( 0-7 j+k+1 \). So the correct answer is \( 0 - 7 j + k + 1 \). Now, let's dive into some relevant insights: Did you know that equations like this one can represent lines in a graph? The variables \( k \) and \( j \) can be thought of as coordinates in a 2D plane! Solving the equation helps you visualize relationships between these variables—it's like drawing a treasure map where each point gives you clues to find arcs of relationships! When manipulating equations like this, a common mistake is forgetting to correctly distribute or combine like terms. Always double-check your algebra! A misstep while simplifying can lead to answers that seem right but ultimately lead you down the wrong path. Keep your work organized, and it becomes much easier to catch those pesky errors!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad